Letramentos docentes: formação, saberes e práticas de ensino - Alves, Ísis Brito (2022)
With a view to enabling more effective teacher preparation and professional practice committed to the quality of teaching and learning processes, a discussion about the role of the teacher in the classroom is considered to be extremely relevant. This research is part of the context of Applied Linguistics and aims to conceptualize and discuss issues related to teacher literacies and its contributions to teacher education. In order to achieve the proposed objective, this work was organized in three moments, which will consist of three articles: a) characterization of Applied Linguistics and its intersections with teacher literacies in order to systematize perspectives for teacher preparation; b) conceptualization of teacher literacies, seeking to demonstrate the contributions of this formative approach to a more articulated professional practice in school contexts; c) production of an educational product, materialized in the form of a proposal for a didactic sequence, with a view to expanding skills related to teacher literacies and the use of multisemiotic texts in the classroom. The first article aims to characterize Applied Linguistics and to discuss the contributions of this area of language studies to teacher education articulated to teaching literacies. The second article presents a characterization of teacher literacies, containing signals proposed by researchers on the expansion of skills related to the articulation between theory and practice, between reflection and action, between planning and execution of didactic activities. The third article consists of the production of a sequence that proposes an analysis of video animation, seeking to contemplate methodological strategies that may contribute to the expansion of skills related to teacher literacies for the forwarding of teaching practices aimed at teaching the reading of multisemiotic texts, preparation this necessary for the current hypermedia context. This research is justified by enabling discussions that enable the expansion of teaching literacies, with a view to contributing to the performance of the Portuguese language teacher in the classroom. Through the research undertaken, it was possible to verify that, although literacies are a recurring theme in research that permeates the scope of teaching, with regard to teacher literacies, it is still necessary that the discussions be deepened and expanded, seeking to contribute significantly to the teacher performance in the classroom. In this way, it is believed that the research will significantly contribute to the teaching performance of the Portuguese language teacher, either through the theoretical discussions proposed here, or through the educational product presented, since it may bring provocations to new discussions. in the field of Applied Linguistics, as well as in the field of mother tongue teaching and learning processes.